1867 Terr. of Wash. Stat. 116, An Act to Incorporate the City of Vancouver, ch. 1, § 32, pt. 16. - (:unkn) unknown (General Publisher, 1867)
To regulate the storage and sale of gunpowder, or other combustible material, and to provide, by all possible and proper means, against danger or risk of damage by fire arising from carelessness, negligence or otherwise.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER